Pengenalan Penggunaan Aplikasi Zoom pada Pembelajaran Daring Pelajaran IPA di SMP Islam Terpadu Al Ghazali Palangka Raya: Dampak Sikap Belajar - Hadma Yuliani; Nur Inayah Syar; Nurul Septiana; Mukhlis Rohmadi; Nadia Azizah; Deni Anggara; Eva Latriana Yuniarti (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Pandemic COVID-19 caused many changes in life, including in the world of education. The learning process that has always been done face-to-face has now been implemented online with various video conferencing. One type of application that can be used as a learning medium is zoom meeting. This service activity was carried out at the Al Ghazali Integrated Islamic Middle School, Palangka Raya with the aim of describing the assessment of student attitudes in participating in online learning for science subjects. The attitude assessment developed is in the form of observations when students participate in online learning through the Zoom Meeting.